Literature Study: The Relationship between Phbs and Diarrhea in School-Age Children - Ibrahim Paneo; Rosmin Ilham; Nirmala Bilale (Journal of Community Health Provision, 2022)
Diarrhea is still one of the main diseases in children that can cause morbidity and mortality. One of the prevention of this diarrhea is the implementation of Clean and Healthy Behavior (PHBS). This study aims to determine the relationship between PHBS and the incidence of diarrheal disease in school-age children. This type of research is a literature study, literature searches using google scholar databases and IOS. The inclusion criteria were in the form of 2016-2020 publications, in full text Indonesian and themed PHBS and diarrhea. The literature was then extracted and analyzed for 10 literatures. The results showed that there was a significant relationship between PHBS and the incidence of diarrheal disease in school-age children. It was concluded that diarrhea often occurs in school-age children, especially if they do not have good clean and healthy living behavior, which further increases the risk of getting diarrhea. The intended link is if this is not done or rarely done, the potential for diarrheal disease will be greater. It is recommended for school children to carry out PHBS in a good school setting to create a health climate and avoid diseases that originate from unhealthy behaviors such as diarrhea.